Contribution of collaborative skill toward construction drawing skill for developing vocational course - Setiawan Abdul Haris (De Gruyter, 2021)
This study aims to support developing research in designing a vocational lesson and learning model for civil engineering education study program by examining students’ collaborative skills toward construction drawing skills as a substantial skill in civil engineering. This study investigated student performance for proposing collaborative learning approaches to improve student skills as needed by industry. It is an ex-post-facto study using 130 samples from several vocational high schools in Indonesia with descriptive statistics and regression for the data analysis. The results show that the collaborative skill is in a fair category of 60.00 and the construction drawing skill is in a good category of 67.49 on a 100 scale. There is a significant and positive influence of collaborative skill (X) toward construction drawing skill (Y) with a linear regression model Ŷ = 31.443 + 1.952X. Furthermore, it presented a correlation coefficient of 0.644, a determination coefficient (R 2) of 0.415, and an adjusted R 2 of 0.410, where it can be concluded that the collaborative skill variable (X) as a predictor in the regression model includes the moderate category, which gives a 41% contribution in explaining the variants of the construction drawing skill (Y) as the dependent variable. It needs special attention to the specific behavioral details of the collaborative skill. The future work is needed to improve collaborative skills that emphasize prioritizing collaboration between peers and learning interdependence.